Parental involvement in children's schooling: the difference between primary and secondary schools in Malaysia - Hashim, Che Noraini; Syed Hassan, Sharifah Sariah; Mansor, Norwati; Badzis, Mastura (2015)

(untitled)
Research in parental involvement in students’ learning has shown significant impact on students’ success and achievement. The aim of the study was to investigate the extent of parental involvement among primary and secondary school children in Malaysia. An extension of parental involvement model by Epstein has been used as a framework of this study to investigate parental involvement among primary and secondary school levers.The factors of parental involvement studied were parenting, volunteering, communicating, collaborating with community, religiosity, school engagement, life goal achievement and learn at home. A total of 916 students responded to the questionnaires. An independent t-test was used to analyze the data. Overall findings indicate a significant difference between parental involvement in primary and secondary school level . Further details and discussions are elaborated.